ANALISIS PENGARUH PENGELUARAN KONSUMSI RUMAH TANGGA DAN PENGELUARAN PEMERINTAH TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN MIMIKA - Abu Bakar (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
This study aims to examine and analyze the significance of the effect of household consumption expenditure and government spending partially on the Mimika Regency Human Development Index, and to test and analyze the significance of the effect of household consumption expenditure and government expenditure simultaneously on the Mimika Regency Human Development Index. The data used in this research is secondary data obtained from BPS Mimika Regency and the Regional Finance and Asset Division of Mimika Regency through documentation techniques. To analyze the data, a semi log multiple regression analysis was used. The results showed that: (a) Household Consumption Expenditure, which is proxied from expenditure for food and non-food consumption, has a significant effect on the Mimika Regency Human Development Index; (b) Government spending, which is proxied from spending on education and health, does not have a significant effect on the Mimika Regency Human Development Index; and (c) Household Consumption Expenditures and Government Expenditures simultaneously have a significant effect on the Mimika Regency Human Development Index.